Feasibility of diesel-biodiesel-alcohol blend fuels for diesel engine / Ali Shahir Shawkat - Ali Shahir, Shawkat (2019)
The energy policies and the ever-growing energy demand of the world require an alternative to fossil fuels. Among the alternative fuels, diesel–ethanol blend or the diesohol blend or the diesel-biodiesel blends might be good options. But these binary blends possess some problems. Diesel-biodiesel blends possess higher density, higher viscosity, lower heating value, poor cold flow properties and higher CN etc., which hinders its use. When biodiesel is added to diesel-bioethanol blends or bioethanol is added to diesel-biodiesel blends then the physicochemical properties of the ternary blends become almost similar to fossil diesel fuel and also remains stable. Thus, the use of ternary blends will eradicate the problems of using binary blends, make the biodiesel and bioethanol more feasible for the CI engines and in the meantime will increase the portion of the oxygen content of the fuel. The objectives of this study is to first develop a density and kinematic viscosity models to calculate the density and viscosity of ternary blends using bioethanol and biodiesel with diesel fuel and compare performance and emission of diesel-biodiesel-bioethanol blends with diesel-biodiesel-propanol, diesel-biodiesel-butanol, diesel-biodiesel-pentanol and diesel-biodiesel-hexanol blends. Five different biodiesels (palm, coconut, soybean, mustard and calophyllum inophyllum biodiesel) have been used with anhydrous bioethanol (99.9% pure) and neat diesel. Initially, density and viscosity models of neat diesel, 5 different biodiesels and bioethanol have been developed with respect to temperature (15°C-100°C). Later, 30 different diesel-biodiesel-bioethanol blends were prepared (each biodiesel×6 blends=30 blends) to measure the density and viscosity at different temperatures. To calculate the density of the diesel-biodiesel-bioethanol blends at 15°C, one density model is proposed with respect to components portion and their individual density which has a very high accuracy rate. To calculate the kinematic viscosity of diesel-biodiesel-bioethanol blends at 40°C, three correlation equations are proposed. To compare the performance and emission between ternary blends, the biodiesel has been kept constant while replacing the alcohol in the blend. Palm biodiesel (PBD) has been selected as the test biodiesel fuel which is considered as the most prospective renewable energy sources of Malaysia in recent years. Initially neat diesel and B20 (80% diesel+20% palm biodiesel) have been tested in the single cylinder Yanmar CI engine. Later, ternary blends of diesel-biodiesel-alcohol were tested. In all the ternary blends, the amount of diesel and PBD were kept constant which were 70% and 20% respectively while only varying the alcohol. Engine tests were conducted at variable speed, ranging from 1000 rpm to 2400 rpm and constant load at full throttle. Engine performance parameters like brake specific fuel consumption (BSFC), brake thermal efficiency (BTE) and engine emissions like nitrogen oxides (NOX), hydrocarbons (HC) and carbon monoxide (CO) were measured. Performance and exhaust emissions variation of the ternary blends from the baseline fuels, i.e. neat diesel and P20, were compared for the assessment of the improvement quantitatively.